2016
DOI: 10.1177/0011000015627197
|View full text |Cite
|
Sign up to set email alerts
|

Intent to Seek Counseling Among Filipinos

Abstract: Cramer's model of help-seeking behavior posited that self-concealment, social support, attitudes toward counseling, and problem severity are essential in understanding individuals' intent to seek counseling. Path analysis results from 359 Filipino university students indicated that the original Cramer's model did not achieve the requisites of good model fit and that social support was not associated with problem severity. After adding loss of face to Cramer's model, we found positive associations with self-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
0
24
0
3
Order By: Relevance
“…Bu açıdan bakıldığında, benlik saygısı düşük olan bireyler diğer insanların vereceği olumsuz geribildirimlerden etkilenebilir ve bunu önlemek veya engellemek için kendilerini saklayabilir. Araştırmacılar olumsuz benlik kavramının temelinde bireyin kendisiyle ilgili yetersiz, sevimsiz/itici, sevilmeye layık olmama gibi çarpıtılmış ve cezalandırıcı akılcı olmayan inançlarının olduğunu belirtmektedir (Ichiyama et al, 1993 (Masuda et al, 2017(Masuda et al, , 2012Masuda & Boone, 2011;Wallace & Constantine, 2005) ve Filipinli üniversite öğrencilerinde (Tuliao et al, 2016) gerçekleştirilen araştırmalar sonucunda cinsiyetin kendini saklamayla ilişkili olmadığı bulunmuştur. Hyde (2005) Bu araştırmada aynı zamanda daha önce psikolojik yardım alan bireylerin kendini saklama eğiliminin daha önce psikolojik yardım almayan bireylerden anlamlı bir şekilde daha yüksek olduğu bulunmuştur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu açıdan bakıldığında, benlik saygısı düşük olan bireyler diğer insanların vereceği olumsuz geribildirimlerden etkilenebilir ve bunu önlemek veya engellemek için kendilerini saklayabilir. Araştırmacılar olumsuz benlik kavramının temelinde bireyin kendisiyle ilgili yetersiz, sevimsiz/itici, sevilmeye layık olmama gibi çarpıtılmış ve cezalandırıcı akılcı olmayan inançlarının olduğunu belirtmektedir (Ichiyama et al, 1993 (Masuda et al, 2017(Masuda et al, , 2012Masuda & Boone, 2011;Wallace & Constantine, 2005) ve Filipinli üniversite öğrencilerinde (Tuliao et al, 2016) gerçekleştirilen araştırmalar sonucunda cinsiyetin kendini saklamayla ilişkili olmadığı bulunmuştur. Hyde (2005) Bu araştırmada aynı zamanda daha önce psikolojik yardım alan bireylerin kendini saklama eğiliminin daha önce psikolojik yardım almayan bireylerden anlamlı bir şekilde daha yüksek olduğu bulunmuştur.…”
Section: Discussionunclassified
“…Cinsiyet en kolay gözlenebilen bireysel farklılıklardan biri olduğundan kadınlar ve erkekler arasındaki bilişsel, kişilik özellikleri ve sosyal davranışlardaki benzerlikler ve farklılıklar araştırmacıların ilgi duyduğu bir konu olmuştur. Kendini saklamanın farklı örneklem gruplarında cinsiyetle ilişkisini inceleyen araştırmalar genel olarak kadınların ve erkeklerin kendini saklama düzeylerinin birbirine benzer olduğunu göstermektedir (Bathje, Kim, Rau, Bassiouny, & Kim, 2014;Kawamura & Frost, 2004;Kelly & Achter, 1995;Masuda & Boone, 2011;Mendoza, Masuda, & Swartout, 2015;Morgan, Ness, & Robinson, 2003;Omori, 2007;Tuliao, Velasquez, Bello, & Pinson, 2016;Wallace & Constantine, 2005;Wismeijer et al, 2008;Yukawa, Tokuda, & Sato, 2007). Ancak bazı araştırmalar kadınların kendini saklama düzeylerinin erkeklerden yüksek olduğunu (Mendoza, Goodnight, Caporino & Masuda, 2018), bazı araştırmalar ise erkeklerin kendini saklama düzeylerinin kadınlardan daha yüksek olduğunu göstermektedir (Cramer & Barry, 1999;Masuda et al, 2009).…”
Section: Introductionunclassified
“…Researchers regard the loss of face concern as one of the important cultural variables, and conducted numerous studies to determine the antecedents, correlates, and consequences of loss of face concern (David, 2010; Leong, Byrne, Hardin, Zhang and Chong, 2018;Leong et al, 2011;Mak and Chen, 2006;Topkaya, 2015a;Topkaya, Şahin and Gençoğlu, 2019;Tuliao, Velasquez, Bello and Pinson, 2016). Research has shown that higher loss of face concern is associated with a range of negative mental health indicators.…”
Section: üNiversite öğRencilerinde Saygınlığını Yitirme Kaygısımentioning
confidence: 99%
“…Studies conducted in different cultures and samples also suggest that, loss of face concern is positively correlated with a number of negative mental health indicators. For example, loss of face concern was positively associated with negative attitudes towards seeking psychological help (David, 2010;Tuliao et al, 2016), high levels of psychological stress (Mak and Chen, 2006), high levels of depressive symptoms (Leong et al , 2018), high level of social anxiety (Zane and Yeh, 2002), low optimism and high level of pessimism (Leong et al, 2018). In addition, loss of face concern is associated with unhealthy negative emotions such as embarrassment and shame (Yeh and Huang, 1996).…”
Section: üNiversite öğRencilerinde Saygınlığını Yitirme Kaygısımentioning
confidence: 99%
See 1 more Smart Citation